Additive Manufacturing of Ceramic‐Based Materials1. Issue 6 (8th April 2014) - Travitzky, Nahum; Bonet, Alexander; Dermeik, Benjamin; Fey, Tobias; Filbert‐Demut, Ina; Schlier, Lorenz; Schlordt, Tobias; Greil, Peter; Travitzky, Nahum; Medvedovski, Eugene
<x xml:space="preserve">Abstract</x> This paper offers a review of present achievements in the field of processing of ceramic‐based materials with complex geometry using the main additive manufacturing (AM) technologies. In AM, the geometrical design of a desired ceramic‐based component is combined with the materials design. In this way, the fabrication times and the product costs of ceramic‐based parts with required properties can be substantially reduced. However, dimensional accuracy and surface finish still remain crucial features in today's AM due to the layer‐by‐layer formation of the parts. In spite of the fact that significant progress has been made in the development of feedstock materials, the most difficult limitations for AM technologies are the restrictions set by material selection for each AM method and aspects considering the inner architectural design of the manufactured parts. Hence, any future progress in the field of AM should be based on the improvement of the existing technologies or, alternatively, the development of new approaches with an emphasis on parts allowing the near‐net formation of ceramic structures, while optimizing the design of new materials and of the part architecture.